Simulation of single-step dimethyl ether synthesis from syngas - Chanida Polsen; Phavanee Narataruksa; Piyapong Hunpinyo; Chaiwat Prapainainar (Energy Reports, 2020)
Dimethyl ether (DME) is an alternative energy that simplest ether. DME has 2 ways to synthesis from syngas. The single-step DME synthesis combined methanol synthesis and methanol dehydration in one reactor. This study is focusing on DME production from synthesis gas by used catalyst as CuO-ZnO-Al2O3/Ú-Al2O3. For the simulation we simulated in Aspen Plus V8.8 and used Langmuir-Hinshelwood Hougen-Watson (LHHW) kinetic model for the reaction rate of DME synthesis in a plug flow reactor with catalyst. Simulation is varying the temperature range between 220~°C to 300~°C and pressure between 20 bar to 80 bar to find the suitable condition for the single-step DME synthesis with CuO-ZnO-Al2O3/Ú-Al2O3 catalyst.
Keywords: 330; Aspen plus; Dimethyl ether; DME synthesis; Kinetic parameter; Simulation of DME